2012
DOI: 10.1021/es2040009
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Biocides from Façades under Natural Weather Conditions

Abstract: Biocides are included in organic building façade coatings as protection against biological attack by algae and fungi but have the potential to enter the environment via leaching into runoff from wind driven rain. The following field study correlates wind driven rain to runoff and measured the release of several commonly used organic biocides (terbutryn, Irgarol 1051, diuron, isoproturon, OIT, DCOIT) in organic façade coatings from four coating systems. During one year of exposure of a west oriented model house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 17 publications
6
96
1
1
Order By: Relevance
“…Usually, typical average wall catch ratios range between 10% and 25% [27,38e40], which means high discrepancies with values simulated in this project. A recent study by Burkhardt et al [41] conducted on a West oriented facade under natural condition estimated a catch ratio of 6.3% after one year of exposure. But while comparing the different results, attention must be paid to measurements, simulations and boundary conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Usually, typical average wall catch ratios range between 10% and 25% [27,38e40], which means high discrepancies with values simulated in this project. A recent study by Burkhardt et al [41] conducted on a West oriented facade under natural condition estimated a catch ratio of 6.3% after one year of exposure. But while comparing the different results, attention must be paid to measurements, simulations and boundary conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the conservation of historic buildings, the design of new buildings and the development of new building materials rely on the correct prediction of moisture loads (Briggen et al 2009). The correct prediction of WDR is also significant in the assessment of environmental risks related to the leaching of harmful biocides and nanoparticles from buildings (Urkhardt et al 2012). WDR deposition in the built environment sees these mentioned effects propagating through different urban surfaces, including, in addition to building facades, roofs, vegetated areas and paved streets, pedestrian ways, etc.…”
Section: Question 1: What Is the Relevance And Significance Of Wdr Inmentioning
confidence: 99%
“…Based on the determined polyacrylate-water partition constants the partitioning of the biocides into the water phase would be in the following order: isoproturon > diuron > carbendazim > N-octylisothiazolinone > iodocarb > cybutryn > terbutryn > propiconazole > tebuconazole > dichloro-N-octylisothiazolinone. During leaching tests from faç-ade render under natural weather conditions Burkhardt et al (2012) analysed seven biocides. Based on that study, the leaching ability could be sorted according to isoproturon > diuron > iodocarb > N-octylisothiazolinone > cybutryn > terbutryn > Table 2 Polyacrylate-water partition constants (log K AcW ) with 95%-confidence interval as well as coefficient of determination (R 2 ) from the non-linear regression model for the studied compounds; N number of data points.…”
Section: Comparison Of Partitioning To Leachingmentioning
confidence: 99%
“…Hence, the total content of biocides in render and exterior paints ranges from 5 to 10 g kg À1 (Burkhardt et al, 2011). Laboratory studies on constantly soaked material, dipping experiments with alternating wet and dry cycles, or forced rain experiments showed that the biocides leach out of the render material in considerable fractions (Schoknecht et al, 2003;Burkhardt et al, 2007;Schoknecht et al, 2009;Burkhardt et al, 2011Burkhardt et al, , 2012Wangler et al, 2012). The leaching process of biocides from render is assumed to be a multistep process: (1) removal from the surface layer which is itself (2) in equilibrium with the deeper layers of the render, from which (3) the surface layer is constantly refilled.…”
Section: Introductionmentioning
confidence: 99%